Nutritional response in a Drosophila yolk protein gene promoter. - Sondergaard, L.; Mauchline, D.; Egetoft, P.; White, N.; Wulff, P.; Bownes, M. (Molecular and General Genetics, 1995)
The yolk protein genes (yps) of Drosophila melanogaster are only expressed in the ovary and fat body of female flies if they are supplied with proteinaceous food. This nutritional response is specific to the yp genes. We have used transgenic flies transformed with a series of constructs bearing deletions in the upstream region of the yp1 and yp2 genes attached to a reporter gene to search for DNA sequences responsible for the nutritional induction specific for yp1 and yp2 genes. Several regions were shown independently of each other to confer nutritional regulation on the expression of the yp1 and yp2 genes. This regulation can be induced both on the yp promoter and the heterologous Drosophila heat-shock 70 (hsp 70) promoter. The redundancy of sequences conferring a nutritional response on the yp genes is similar to that observed for the female specificity of these genes and suggest that several DNA binding proteins interact to provide the correct regulation of these genes. These results suggest that nutrition acts to modify the level of a trans-acting factor in the fat body. Northern blot analysis showed that the transcript levels from the dsx gene are not affected by nutrition, indicating that the response is not mediated via the dsx gene.